Penganggaran Berbasis Kinerja pada Dinas Koperasi, Usaha Kecil, Menengah, Perdagangan, dan Perindustrian Kota Cirebon - Johana Noviantika, Ribka; Myrna, Rita (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This study aims to analyze the performance-based budgeting implemented by the Cooperative, Small and Medium Enterprises, Trade, and Industry Office of Cirebon City. The theoretical framework for this research is the performance-based budgeting cycle proposed by Nurkholis and Khusaini (2019). A qualitative research method was employed, utilizing data collection techniques such as interviews, observations, and documentation. The results indicate that the Cooperative, Small and Medium Enterprises, Trade, and Industry Office of Cirebon City has implemented four stages of the performance-based budgeting cycle in accordance with the theory of Nurkholis and Khusaini, namely determining vision and mission, goals, and targets, determining performance indicators, evaluating and making decisions on program selection and priorities, and analyzing cost standards. However, challenges persist in the stage of determining performance indicator, evaluating and making decisions on program selection and priorities, and analyzing cost standards. This study suggests aligning output and outcome targets with available inputs, prioritizing programs based on the capacity of work units, and adjusting cost standards to reflect market prices.